Acid/base-regulated reversible electron transfer disproportionation of N–N linked bicarbazole and biacridine derivatives1. Issue 7 (15th July 2015) - Pandit, Palash; Yamamoto, Koji; Nakamura, Toshikazu; Nishimura, Katsuyuki; Kurashige, Yuki; Yanai, Takeshi; Nakamura, Go; Masaoka, Shigeyuki; Furukawa, Ko; Yakiyama, Yumi; Kawano, Masaki; Higashibayashi, Shuhei
<x xml:space="preserve">Abstract</x> New acid/base-responsive organic compounds were discovered to undergo electron transfer disproportionation.